Heave buoy energy converters simulation of heave buoy response to wave in Malaysian water - Mohamad Abu Ubaidah Amir; Rina Mohd Sharip; Wan Baderul Hisan Wan Muda; Mohd Afizi Mohd Shukran; Hardy Azmir Anuar; Omar Zakaria (LCP : conference papers, 2014)
Abstract : Wave energy converter (WEC) designs are always discussed in order to find an optimum design to generate power. The power output from wave energy converters may be increase by controlling the oscillation in order to approach an optimum interaction between the WEC and the incident wave. However, in order to control the oscillation of the heave buoy, the wave profile and the decive's response on Malaysian water using MathCAD software. The results shows that the heave buoy give a good heave response with regards of the wave phase. In this particular area, it is estimated that the wave force can produce as much 4 x 10 k W/m. From the response, the strategies to optimize power output can be proposed in order to maximize the active power to generate an optimum power output